Validation of the French version of the student engagement instrument - Lessard, Anne; Lopez, Amanda; Diallo, Thierno (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
The purpose of this study is to explore the psychometric properties of the French version of the Student Engagement Instrument in order to perform a cross-cultural validation of its factorial structure, based on a sample of 919 French Canadian high school students. Results confirm the reliability of the instrument with good internal consistency (Cronbach’s alpha between .76 and .84). Confirmatory factor analysis shows the validity of the six scales composing the French version of the instrument. Results are significant as there were no standardized instruments with which to evaluate student engagement in high school students in French. Student engagement represents an important intervention target towards improving student achievement and preventing dropout.